Road Surface Distress Analysis Using Bina Marga Method and GIS on Ngimbang–Sambeng Road Section, Lamongan - Muhammad Rafli Bimo Prasetyo; Fithri Estikhamah; Bagas Aryaseta (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Roads are critical land transportation infrastructure that support community mobility, the movement of goods and services, and regional economic development. Increasing traffic volume and road utilization intensity often accelerate pavement deterioration, which is manifested in various forms of surface distress. Therefore, a systematic assessment of road conditions is essential to identify the extent of damage and determine appropriate maintenance priorities. This study aims to evaluate pavement damage using the Bina Marga method and to map road condition spatially using a Geographic Information System (GIS) on the Ngimbang–Sambeng Road Section in Lamongan Regency. The studied road section has a total length of 7.19 km and was divided into eight segments for analysis. The research employed a visual pavement survey to identify the types and dimensions of distress, complemented by a traffic survey to determine the Average Daily Traffic (ADT). The results show that the road section falls into traffic class 6, with an average pavement damage percentage of 23.7%. The dominant distress types identified were alligator cracking, longitudinal cracking, potholes, and surface deformation. Based on the Bina Marga analysis, the road condition value ranged from 4 to 8, while the priority ranking value ranged from 3 to 7. The findings indicate that the appropriate treatment strategies include routine maintenance, periodic maintenance, and road improvement for specific segments. Furthermore, GIS-based mapping provides a clear spatial visualization of pavement damage distribution, which can support more effective and data-driven decision-making for road maintenance and rehabilitation planning. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities